Comparison of Multinational Medical School Students Experiences in the Face of the COVID-19 Pandemic: A Qualitative Analysis - Skoczek, Alexandra C.; Ruane, Patrick W.; Onley, Cassidy; Haydel, Torhiana; Ortega, Maria Valeria; Sutphin, H. Dean; Stoner, Alexis M. (International Journal of Medical Students, 2023)
Background: In the midst of the COVID-19 pandemic, countries, and governments around the world have implemented different measures and guidelines for the containment and mitigation of the COVID-19 virus. In addition to implemented policies and initiatives, social media and personal beliefs have affected medical students’ social, emotional, financial, and academic stability and success both domestically and internationally. The objective of this study was to assess medical student's perspectives, attitudes, and insight in the face of the COVID-19 pandemic and determine if differences exist between countries. Methods: This qualitative study, recruited students enrolled in the Global Seminar for Health and Environment elective course in their respective medical schools to complete a weekly, non-graded journaling assignment for 6 weeks. To measure outcomes, open-ended questions within the assignment asked students across four different countries questions regarding the COVID-19 pandemic including personal beliefs and knowledge, policies and initiatives within their country, global policies and initiatives, and social media presentations. Thematic analysis was then completed using the QCoder package in R Studio. Results: Both internationally and in the US, COVID-19 has had a large impact on medical students; however, their perspectives are distinct in personal beliefs, policies, and social media. International medical students believed that their country's COVID-19 response contained more restrictions than the global response, with the theme being expressed in 11 of 67 responses (16.4%) compared to 1 of 75 responses (1.3%) of US responses. This was enforced by the US medical students' views that the US had fewer COVID-19 restrictions. US medical students had a higher number of responses with the theme “more restrictions internationally” which was present in 21 of 75 responses (28%). US medical students were more likely to express a decrease in the number of academic opportunities and academic performance. The theme “decrease in academic opportunities and performance” was present in 15 of 75 US responses (20%) compared to 9 of 67 international responses (13.4%). A US response containing this theme was as follows: “I have had to adjust to a new way of doing school, mainly online, as well as coming to terms with the fact that I am not getting to experience many of the social aspects of medical school that I was looking forward to.” The US responses showed less of a mental health impact and expressed stronger negative views on how COVID-19 was handled with 40 of 75 US responses (53.3%) reporting the theme “need better initiatives and policies. Conclusion: The COVID-19 pandemic continues to affect medical students globally. The current study was limited by responses and student participation each week. Future studies aimed at analyzing specific COVID-19 policies around the world and the extent of the pandemic’s impact on mental health may provide greater insight into medical students' beliefs, attitudes, and well being which have been challenged over the last year. Regardless, it must be acknowledged that the medical school experience has changed for both international and United States medical students and affected them not only academically but mentally, socially, and financially.